CuFe2O4 Nanofiber Incorporated with a Three-Dimensional Graphene Sheet Composite Electrode for Supercapacitor and Electrochemical Sensor Application - Sivaramakrishnan Vinothini; Arjunan Karthi Keyan; Subramanian Sakthinathan; Te-Wei Chiu; Naratip Vittayakorn (My University, 2024)
The demand for regenerative energy and electric automotive applications has grown in recent decades. Supercapacitors have multiple applications in consumer alternative electronic products due to their excellent energy density, rapid charge/discharge time, and safety. CuFe2O4-incorporated three-dimensional graphene sheet (3DGS) nanocomposites were studied by different characterization studies such as X-ray diffraction, transmission electron microscopy, and scanning electron microscopy. The electrochemical studies were based on cyclic voltammetry (CV), galvanostatic charge–discharge (GCD), and electrochemical impedance spectroscopy (EIS) measurements. As prepared, 3DGS/CuFe2O4 nanocomposites exhibited an excellent surface area, high energy storage with appreciable durability, and excellent electrocatalysis properties. A supercapacitor with 3DGS/CuFe2O4-coated nickel foam (NF) electrodes exhibited an excellent specific capacitance of 488.98 Fg−1, a higher current density, as well as a higher power density. After charge–discharge cycles in a 2.0 M KOH aqueous electrolyte solution, the 3DGS/CuFe2O4/NF electrodes exhibited an outstanding cyclic stability of roughly 95% at 10 Ag−1, indicating that the prepared nanocomposites could have the potential for energy storage applications. Moreover, the 3DGS/CuFe2O4 electrode exhibited an excellent electrochemical detection of chloramphenicol with a detection limit of 0.5 µM, linear range of 5–400 µM, and electrode sensitivity of 3.7478 µA µM−1 cm−2.
Keywords: Supercapacitor Materials and Fabrication